1996
DOI: 10.1002/(sici)1097-0274(199608)30:2<180::aid-ajim9>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in a cohort of pentachlorophenol manufacturing workers, 1940-1989

Abstract: Mortality in a cohort of 770 workers with potential pentachlorophenol (PCP) exposure was evaluated from 1940 through 1989. The study cohort is a subset of a larger cohort of workers with potential exposure to higher chlorinated dioxins. Total mortality and cancer mortality, in the PCP cohort were slightly lower than expected in comparison to the U.S. white male population. There were 229 total deaths with 242.5 expected (SMR = 94, 95% confidence interval 83–108), and 50 cancer deaths with 52.6 expected (SMR = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 11 publications
0
31
2
Order By: Relevance
“…Case reports and case-control studies of hematopoietic cancers published in the 1980s and 1990s indicated the risk of non-Hodgkin lymphoma, soft-tissue sarcoma and multiple myeloma in relation to pentachlorophenol exposure for (Greene et al, 1978;Bishop et al, 1981;Pearce et al, 1986;Smith et al, 1992;Hardell et al, 1994;Hardell et al, 1995;Kogevinas et al, 1995). In the 1990s and 2000s, four cohort studies reported the results between cancer risk and PCP exposure, and most of them reported weak or no risk of exposure to PCP, the authors infer the non-significant results might due to the less study population and healthy worker effects (Hertzman et al, 1997;Demers et al, 2006;Ramlow et al, 1996;Ruder et al, 2011). After it has been forbidden to use in many countries, a worldwide research suggests that in indoor air, bodies of water, and freshwater sediments around the world, PCP levels has declined over time (Zheng et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Case reports and case-control studies of hematopoietic cancers published in the 1980s and 1990s indicated the risk of non-Hodgkin lymphoma, soft-tissue sarcoma and multiple myeloma in relation to pentachlorophenol exposure for (Greene et al, 1978;Bishop et al, 1981;Pearce et al, 1986;Smith et al, 1992;Hardell et al, 1994;Hardell et al, 1995;Kogevinas et al, 1995). In the 1990s and 2000s, four cohort studies reported the results between cancer risk and PCP exposure, and most of them reported weak or no risk of exposure to PCP, the authors infer the non-significant results might due to the less study population and healthy worker effects (Hertzman et al, 1997;Demers et al, 2006;Ramlow et al, 1996;Ruder et al, 2011). After it has been forbidden to use in many countries, a worldwide research suggests that in indoor air, bodies of water, and freshwater sediments around the world, PCP levels has declined over time (Zheng et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The most consistently observed findings have been excesses of non-Hodgkin's lymphoma [3][4][5] and soft tissue sarcoma [6][7][8][9][10], although excesses of multiple myeloma [11,12], lung [13,14], kidney [13,15], nasopharyngeal and sinonasal cancers [16] have also been observed. However, the results of studies have not always been consistent [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of studies have not always been consistent [2]. In addition, few studies have provided results specifically for pentachlorophenol or tetrachlorophenol, all with relatively small numbers of exposed people [5,15,17]. The evidence regarding the human carcinogenicity of polychlorophenols and their salts was most recently classified as ''limited'' by the International Agency for Research on Cancer (IARC) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The most informative epidemiologic studies of chronic effects of TCDD exposure were conducted among U.S. Air Force personnel exposed to TCDD-contaminated pesticides (13)(14)(15)(16), pesticide users and chemical production workers, including groups of workers involved in industrial accidents (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), and populations of contaminated communities in Missouri in the United States and Seveso, Italy (27)(28)(29)(30). Possible long-term nonneoplastic consequences of TCDD exposure appear to be altered male reproductive hormone levels, lipid metabolism, and thyroid function, chronic elevated levels of the hepatic enzyme y-glutamyl transferase, persistent chloracne, reproductive toxicity, increased risk of diabetes, and immunologic, renal, respiratory, and cardiovascular disorders (1,2).…”
Section: Introductionmentioning
confidence: 99%